A Source Book in Chinese Philosophy - Chan, Wing-Tsit (Book collections on Project MUSE., 1969)
A Source Book in Chinese Philosophy is a milestone along the complex and difficult road to significant understanding by Westerners of the Asian peoples and a monumental contribution to the cause of philosophy. It is the first anthology of Chinese philosophy to cover its entire historical development. It provides substantial selections from all the great thinkers and schools in every period--ancient, medieval, modern, and contemporary--and includes in their entirety some of the most important classical texts. It deals with the fundamental and technical as well as the more general aspects of Chi.